2012
DOI: 10.7598/cst2012.206
|View full text |Cite
|
Sign up to set email alerts
|

Deflouridation from Aqueous Solutions Using Alum

Abstract: This research work has been designed to remove the fluoride from aqueous solutions using alum by bench scale experiments. The defluoridating agent, which is easily available even in rural areas, has been selected. The known concentrations of fluoride solution were prepared. The removal of fluorides by the defluoridating agent was studied up to 4 hours for all the fluoride concentrations. The variations in the percentage removal and attainment of equilibrium were recorded. The solutions of 2, 4, 6, 8 and 10 mg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 12 publications
2
4
0
Order By: Relevance
“…Other higher amount of Zn in stem and leaf of the plant were found on 180 and 120 harvesting days with a concentration 29.75 ± 4.40 and 27.88 ± 2.21 mg/kg respectively. This study agreed with the similar experiment carried out on Zn uptake using different plant species by Subhashini et al, 40 , they reported that Acalypha indica and Ruellia tuberosa accumulated Zn in the tissues following the trend root > stem > leaf. 40 .…”
Section: Zincsupporting
confidence: 93%
“…Other higher amount of Zn in stem and leaf of the plant were found on 180 and 120 harvesting days with a concentration 29.75 ± 4.40 and 27.88 ± 2.21 mg/kg respectively. This study agreed with the similar experiment carried out on Zn uptake using different plant species by Subhashini et al, 40 , they reported that Acalypha indica and Ruellia tuberosa accumulated Zn in the tissues following the trend root > stem > leaf. 40 .…”
Section: Zincsupporting
confidence: 93%
“…In the treatment of C2 and C3, there was a reduction of potassium (12 mg/ kg, 16 mg/kg) and phosphate (53 mg/kg, 61 mg/kg), but in C4 and C5, the micro-organisms in the soil were unable to uptake these minerals, due to the high concentration of sludge 20 . Helianthus annuus was able to uptake Pb and Ni from ETP mixed soil (72 mg/kg and 44,410 mg/kg), which was quite low compared to the plant Catharanthus roseus which up took Pb and Ni by 67.34 mg/kg and 45.75 mg/kg 21 . Helianthus annuus was able to survive and uptake chromium (183704 mg/kg) from pre-treated sludge.…”
Section: Resultsmentioning
confidence: 88%
“…Similarly, the rocks in southern India are rich with fluoride which forms the major reason for fluoride contamination in groundwater , and the granites in the districts of Andhra Pradesh contain much higher fluoride than the world average fluoride concentration of 810 mg/kg . Fluorosis was first detectedin India, among cattle and humans in Andhra Pradesh .In India, approximately 60-65 million people drink fluoride contaminated groundwater, and the number affected by fluorosis is estimated at 2.5-6 million, predominately children [5][6]. In India, the excessive presence of fluorides in groundwater is present in nearly 177 districts covering 19 states.…”
Section: Introductionmentioning
confidence: 99%